The Cartilage-Bone Interface - Hoemann, Caroline D.; Lafantaisie-Favreau, Charles-Hubert; Lascau-Coman, Viorica; Chen, Gaoping; Guzmán-Morales, Jessica (The Journal of Knee Surgery, 2012)
In the knee joint, the purpose of the cartilage-bone interface is to maintain structural integrity of the osteochondral unit during walking, kneeling, pivoting, and jumping–during which tensile, compressive, and shear forces are transmitted from the viscoelastic articular cartilage layer to the much stiffer mineralized end of the long bone. Mature articular cartilage is integrated with subchondral bone through a ~20 to ~250 µm thick layer of calcified cartilage. Inside the calcified cartilage layer, perpendicular chondrocyte-derived collagen type II fibers become structurally cemented to collagen type I osteoid deposited by osteoblasts. The mature mineralization front is delineated by a thin ~5 µm undulating tidemark structure that forms at the base of articular cartilage. Growth plate cartilage is anchored to epiphyseal bone, sometimes via a thin layer of calcified cartilage and tidemark, while the hypertrophic edge does not form a tidemark and undergoes continual vascular invasion and endochondral ossification (EO) until skeletal maturity upon which the growth plates are fully resorbed and replaced by bone. In this review, the formation of the cartilage-bone interface during skeletal development and cartilage repair, and its structure and composition are presented. Animal models and human anatomical studies show that the tidemark is a dynamic structure that forms within a purely collagen type II-positive and collagen type I-negative hyaline cartilage matrix. Cartilage repair strategies that elicit fibrocartilage, a mixture of collagen type I and type II, are predicted to show little tidemark/calcified cartilage regeneration and to develop a less stable repair tissue-bone interface. The tidemark can be regenerated through a bone marrow-driven growth process of EO near the articular surface.
Keywords: endochondral ossification; tidemark; calcified cartilage; articular cartilage; collagen type II; collagen type I; bone; blood vessels; growth plate; glycosaminoglycan